Memerangi Tindak Pidana Kekerasan Seksual - Edrisy, Ibrahim Fikma; Dewi, Ni Putu Paramita; Sumartini, Ni Wayan Eka; Cristiana, Edelweisia (Satya Dharma : Jurnal Ilmu Hukum, 2023)
Sexual violence is the most common case experienced by women when compared to physical and psychological violence that occurs in 2022. It is not uncommon for sexual violence to occur in educational environments, one of which is in universities. Several regulations were made in an effort to prevent and handle sexual violence, including Permendikbudristek Nomor 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments, the Criminal Act on Sexual Violence, and supported in the Criminal Code Number 1 of 2023 This article was written with the aim that it is important to have knowledge and insight regarding the existence of comprehensive legal regulations as a legal umbrella in dealing with criminal acts of sexual violence. The issues raised in this article include legal regulations that can accommodate the needs of victims of sexual violence, how law enforcement officials respond in understanding cases of sexual violence, and legal analysis of the three regulations regarding sexual violence. The normative research method used in this paper is to identify the legal rules written in Law No. 12 of 2022 concerning Crimes of Sexual Violence, Criminal Code Number 1 of 2023, and Minister of Education and Culture Regulation Number 30 of 2021. The results of this research show that the UUTPKS accommodates the restoration of the rights of victims of sexual violence that were previously denied to the victims. Difficulty in describing sexual violence is an inhibiting factor in law enforcement in the field by law enforcement officers. Thus, it is very important to provide information to the public about criminal acts of sexual violence. Victims of sexual violence receive protection, treatment and assistance in efforts to restore their rights.